Testing of midwife neonatal resuscitation skills with a simulator manikin in a low‐risk delivery unit. Issue 4 (10th June 2013) - Rovamo, Liisa M.; Mattila, Minna‐Maria; Andersson, Sture; Rosenberg, Per H.
Abstract: Background: Expertise in neonatal resuscitation is essential for personnel involved in the care of newborns. In this observational cohort study the skills of 52 midwives in a simulated scenario were assessed. Methods: A total of 52 midwives in a low‐risk unit and five specialist nurses in a high‐risk unit were tested to establish their competence in newborn resuscitation. The 52 midwives were divided into groups 1 ( n = 39; no pretest training) and 2 ( n = 13; 1 day training prior to study). The video‐recorded test scenario was a newborn with asphyxia. Thirty items were graded by a neonatologist and nursing team in real time. Using the Angoff method, a pass score was 18.71 for skills that were graded 0 or 1. Results: The average score of specialist nurses was 26 (range, 23–29). A total of 49% of midwives in group 1 and 92% in group 2 passed the test. The average score was 17.7 (range, 9–25) in group 1 and 21.9 (range, 17–27) in group 2. A total of 27% and 77% of midwives in groups 1 and 2, respectively, carried out ventilation at a frequency as per the algorithm. Mask leakage was higher in group 1 (44%) versus group 2 (23%). Five and three midwives in groups 1 and 2, respectively, overexpanded the lungs. Conclusion: Many midwives had imperfect resuscitation skills. A 1 day course improved such skills. The standard scenario is an objective and useful performance marker in assessing and documenting improvements in competence in delivery room resuscitation.